Effect of redistribution of internal forces on fire resistance of flexural reinforced concrete members - Bednarek, Zoja (Journal of Civil Engineering and Management, 2003)
In this paper the author presents the results of experiments with the three steel grades under thermal conditions of the standard fire with account of the change of stress in steel samples, similar to changes of stress in the reinforcement, resulting from redistribution of bending moments. The major purpose of the experiments was to find out whether it would be possible to take into account the redistribution of bending moments of reinforced concrete members by the method developed by the author for determining the critical temperature and the time till failure of reinforcement of the concrete bended members.First Published Online: 26 Jul 2012